Is pregnancy termination being used as a family planning method in the Free State? - F. Lang; G. Joubert; E.A.M. Prinsloo (South African Family Practice)
Background: This study determined the profile of women seeking termination of pregnancy (TOP) in the Free State and whether TOP was used as a family planning method.